IMPROVEMENT THE PREVENTING SYSTEM AND REDUCING REDUNDANT SYMPTOMS FOR THE BUDDHIST MONK WITH DIABETES AND HYPERTENSION IN NAKHON RATCHASIMA PROVINCE - Atcharoek, ฺิBenyapa (Journal of MCU Nakhondhat, 2023)
The objectives of this research article are 1) to study the guidelines for preventing and reducing recurring illnesses among monks with diabetes hypertension in Nakhon Ratchasima Province 2) To develop a process to prevent and reduce repeated illnesses among monks with diabetes high blood pressure in Nakhon Ratchasima province and 3) Presenting a system to prevent and reduce repeated illnesses for monks with diabetes hypertension in Nakhon Ratchasima Province using research mix methods, the population included monks with diabetes High blood pressure who lives in the temple area in Dan Kwian Subdistrict and temples in Hua Thale Subdistrict, Nakhon Ratchasima Province, 30 people. 30 important informants people. The representative monk Community leaders public health volunteers at the temple and public health officials at the subdistrict health promoting hospital. Data analysis by describing the results of the research found that: 1) Study of the guidelines to prevent and reduce repeated illnesses among monks with diabetes hypertension in Nakhon Ratchasima Province consists of 1) the monk health database create a database system for monks to know information linking monks is information with benefits in the health insurance system. 2) Health calendar Use the medicine calendar to have an understanding of how to take medicine. 3) Behavioral aspects Ill monks must take care of themselves. Adjust to live with chronic disease and take care of your own health. 4) With cooperation relevant agencies cooperate in caring for the health of monks. 2) Develop a process to prevent and reduce recurring illnesses among monks with diabetes hypertension in Nakhon Ratchasima Province with “Calendar, Diabetes Medicine, High Blood Pressure” 3) Presenting a system to prevent and reduce repeated illnesses for monks with diabetes hypertension in Nakhon Ratchasima Province consists of collecting data and coordinating information with local officials. Practice yourselves by learning and changing the behavior of monks. Network agencies join in initiating cooperation with monks to receive medical treatment rights. Support budget for monks' health care.